2020
DOI: 10.1101/2020.07.07.186452
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Auditory detection is modulated by theta phase of silent lip movements

Abstract: SUMMARYAudiovisual speech perception relies on our expertise to map a speaker’s lip movements with speech sounds. This multimodal matching is facilitated by salient syllable features that align lip movements and acoustic envelope signals in the 4 – 8 Hz theta band (Chandrasekaran et al., 2009). The predominance of theta rhythms in speech processing has been firmly established by studies showing that neural oscillations track the acoustic envelope in the primary auditory cortex … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, other sources of interference with putative MMN measurements may emerge as unintended consequences of subject behaviour during passive auditory oddball experiments. For instance, two common approaches are to instruct the subject to watch a silent film or read a book, which present different sets of cues that could unintentionally modulate the auditory response in different respects (Biau et al, 2021; Rayner and Clifton, 2009; Zoefel, 2021). As such, demonstrating that MMN reflects a specific prediction-error signal is challenging, and the balance of evidence from the current study leans decidedly towards the hypothesis that intensity MMN reflects modulation of obligatory sensory components of the ERP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other sources of interference with putative MMN measurements may emerge as unintended consequences of subject behaviour during passive auditory oddball experiments. For instance, two common approaches are to instruct the subject to watch a silent film or read a book, which present different sets of cues that could unintentionally modulate the auditory response in different respects (Biau et al, 2021; Rayner and Clifton, 2009; Zoefel, 2021). As such, demonstrating that MMN reflects a specific prediction-error signal is challenging, and the balance of evidence from the current study leans decidedly towards the hypothesis that intensity MMN reflects modulation of obligatory sensory components of the ERP.…”
Section: Discussionmentioning
confidence: 99%
“…We illustrate our line of argumentation with an example. Recent research has shown that the rhythm of visual speech cues modulates the ability to detect an auditory target (Biau et al, 2021). This effect could merely reflect a passive relay of visual information to the auditory system and lead to a rhythmic modulation of auditory perception only because the information itself is rhythmic.…”
Section: Why We Need To Know: Shared Propertiesmentioning
confidence: 99%
“…We illustrate our line of argumentation with an example. Recent research has shown that the rhythm of visual speech cues modulates the ability to detect an auditory target [16]. This effect could merely reflect a passive relay of visual information to the auditory system and lead to a rhythmic modulation of auditory perception only because the information itself is rhythmic.…”
Section: Why We Need To Know: Shared Propertiesmentioning
confidence: 99%